Tuberculosis caused by Mycobacterium africanum: Knowns and unknowns. - Marta L Silva; Baltazar Cá; Nuno S Osório; Pedro N S Rodrigues; Ana Raquel Maceiras; Margarida Saraiva (PLoS Pathogens, 2022)
Tuberculosis (TB), one of the deadliest threats to human health, is mainly caused by 2 highly related and human-adapted bacteria broadly known as Mycobacterium tuberculosis and Mycobacterium africanum. Whereas M. tuberculosis is widely spread, M. africanum is restricted to West Africa, where it remains a significant cause of tuberculosis. Although several differences have been identified between these 2 pathogens, M. africanum remains a lot less studied than M. tuberculosis. Here, we discuss the genetic, phenotypic, and clinical similarities and differences between strains of M. tuberculosis and M. africanum. We also discuss our current knowledge on the immune response to M. africanum and how it possibly articulates with distinct disease progression and with the geographical restriction attributed to this pathogen. Understanding the functional impact of the diversity existing in TB-causing bacteria, as well as incorporating this diversity in TB research, will contribute to the development of better, more specific approaches to tackle TB.